Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.32604/csse.2022.022247
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Evaluating a Collaborative Knowledge Management Framework for Leaf Disease Detection

Abstract: Knowledge Management (KM) has become a dynamic concept for inquiry in research. The management of knowledge from multiple sources requires a systematic approach that can facilitate capturing all important aspects related to a particular discipline, several KM frameworks have been designed to serve this purpose. This research aims to propose a Collaborative Knowledge Management (CKM) Framework that bridges gaps and overcomes weaknesses in existing frameworks. The paper also validates the framework by evaluating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
(41 reference statements)
2
2
0
Order By: Relevance
“…According to JOMKSM, UserSat is positively associated with IU and NB. These findings are also supported by previous research by Bashir et al [17] and Al-Hattami & Kabra [16]. Research done by Wang and Yang [15] also supports the finding about UserSat is positively associated with NB.…”
Section: Figure 2 Scientific Modelsupporting
confidence: 88%
See 3 more Smart Citations
“…According to JOMKSM, UserSat is positively associated with IU and NB. These findings are also supported by previous research by Bashir et al [17] and Al-Hattami & Kabra [16]. Research done by Wang and Yang [15] also supports the finding about UserSat is positively associated with NB.…”
Section: Figure 2 Scientific Modelsupporting
confidence: 88%
“…This finding is also supported by research done by Al-Hattami & Kabra [16]. Aside from NB, research done by Bashir et al [17], Halawi et al [18], and Mohammed [13] found that the IU dimension also positively affects UserSat dimension.…”
Section: Figure 2 Scientific Modelsupporting
confidence: 71%
See 2 more Smart Citations